Tinjauan Kelengkapan Pengisian Formulir Ringkasan Masuk & Keluar Pada Kasus Pasien Penyakit Dalam Rumah Sakit Bhayangkara Makassar - Putri Amalia; Syamsuddin; Mikawati; Nurintan Malik (Indonesian Journal of Health Information Management, 2026)
Abstract Backround: The completeness of the entry and exit summary form is very important because it has a function as a source of information about the course of the disease, indexing the disease and as a source of information in preparing hospital reports. As explained in the Hospital SPM, the completeness of medical records, especially the entry & exit summary form, must be filled in at least 100%. Objective: To find out the completeness of filling out the entry & exit summary form in the case of internal medicine patients at Bhayangkara Makassar Hospital. Method: This study uses a descriptive method with a quantitative approach, a total sample of 57 medical records with sample withdrawal using the slovin formula. Data collection with observation and interviews was then processed using the IBM SPSS 23 application. Results: The results of the study were complete patient identification review (95%), incomplete (5%), complete important reporting review (63%), incomplete (37%), complete authentication review (91%), incomplete (9%), complete and correct documentation review (98%), incomplete (2%). Conclusion: The completeness of filling out the summary form for entering and exiting Bhayangkara Hospital Makassar is still incomplete. It is hoped that regular socialization and evaluation will be held as well as rewards and punishments will be given to officers involved in filling in medical records.